Subchronic Peripheral Neuregulin-1 Increases Ventral Hippocampal Neurogenesis and Induces Antidepressant-Like Effects - Mahar, Ian (Public Library of Science, 2011)
BACKGROUND: Adult hippocampal neurogenesis has been implicated in the mechanism of antidepressant action, and neurotrophic factors can mediate the neurogenic changes underlying these effects. The neurotrophic factor neuregulin-1 (NRG1) is involved in many aspects of brain development, from cell fate determination to neuronal maturation. However, nothing is known about the influence of NRG1 on neurodevelopmental processes occurring in the mature hippocampus. METHODS: Adult male mice were given subcutaneous NRG1 or saline to assess dentate gyrus proliferation and neurogenesis, as well as cell fate determination. Mice also underwent behavioral testing. Expression of ErbB3 and ErbB4 NRG1 receptors in newborn dentate gyrus cells was assessed at various time points between birth and maturity. The phenotype of ErbB-expressing progenitor cells was also characterized with cell type-specific markers. RESULTS: The current study shows that subchronic peripheral NRG1β administration selectively increased cell proliferation (by 71%) and neurogenesis (by 50%) in the caudal dentate gyrus within the ventral hippocampus. This pro-proliferative effect did not alter neuronal fate, and may have been mediated by ErbB3 receptors, which were expressed by newborn dentate gyrus cells from cell division to maturity and colocalized with SOX2 in the subgranular zone. Furthermore, four weeks after cessation of subchronic treatment, animals displayed robust antidepressant-like behavior in the absence of changes in locomotor activity, whereas acute treatment did not produce antidepressant effects. CONCLUSIONS: These results show that neuregulin-1β has pro-proliferative, neurogenic and antidepressant properties, further highlight the importance of peripheral neurotrophic factors in neurogenesis and mood, and support the role of hippocampal neurogenesis in mediating antidepressant effects.